2021
DOI: 10.1136/bcr-2021-242146
|View full text |Cite
|
Sign up to set email alerts
|

Multiple, large intra-abdominal cystic lesions and iron deficiency anaemia as the presenting symptoms of SDHD gastrointestinal stromal tumour (GIST) in a young sub-Saharan woman

Abstract: We report the case of a 27-year-old female patient from sub-Saharan Africa who presented with non-specific abdominal complaints, iron deficiency anaemia and multiple, large intra-abdominal cystic lesions on imaging. The lesions appeared to be a most unusual presentation of gastrointestinal stromal tumour (GIST). GIST is a sarcomatous tumour that comprises only 0.2% of all gastrointestinal (GI) tumours; it is the most common mesenchymal malignancy of the GI tract. Our patient had the succinate dehydrogenase-def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…The management of patients with gastrointestinal stromal tumors (GISTs) involves a multidisciplinary team that includes pathologists, medical oncologists, surgeons, anaesthesiologists, and imaging experts. Four standard treatment approaches are utilized: [5,10,12].…”
Section: Case 3 -Extra Luminal Transverse Colon Gistmentioning
confidence: 99%
See 3 more Smart Citations
“…The management of patients with gastrointestinal stromal tumors (GISTs) involves a multidisciplinary team that includes pathologists, medical oncologists, surgeons, anaesthesiologists, and imaging experts. Four standard treatment approaches are utilized: [5,10,12].…”
Section: Case 3 -Extra Luminal Transverse Colon Gistmentioning
confidence: 99%
“…The goal of surgery is complete resection with an intact pseudo-capsule and negative microscopic margins. The type of surgery depends on the size and location of the tumor in the GI tract: [4,6,12].…”
Section: Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…A case of SDHdeficient GIST with multiple entirely cystic lesions has been reported; however, the reported case showed multiple lesions similar to the usual SDH-deficient GIST. 4 One study regarding GISTs with remarkable cystic changes revealed that nine cases out of 20 cases did not harbor KIT or PDGFR-α mutations. 5 Although SDH deficiency was not investigated in the study, 5 some of such KIT-negative GISTs with remarkable cystic changes might be SDH-deficient GISTs.…”
mentioning
confidence: 99%